Protein expression, crystallization and in-silico studies on cytochrome P450 Oxidoreductase wildtype and mutant variants - Shafqat, Naeem; Amdani, Siti Nornadhirah; Long, Chiau Ming * (Marmara University Press, 2024)
Cytochrome P450 oxidoreductase (POR) is a crucial membrane-bound enzyme that facilitates the transfer of electrons to all cytochrome P450 (CYP450) enzymes. Several mutations in the POR gene have been reported to cause cytochrome P450 oxidoreductase deficiency (PORD), an autosomal recessive genetic disorder. This study explored the consequences of seven POR missense mutations (Y181D, A287P, R457H, R498P, C569Y, Y607C, and H628P), which have been documented in PORD patients, on the structural integrity and stability of the POR enzyme in vitro. The comparison between these mutants and the wild-type POR focused on in vitro protein expression, purification, and crystallization characteristics. The mutation-induced alterations in the POR architecture significantly influenced the protein's expression and crystallization capabilities. The magnitude of these effects on the enzyme's behavior varied from moderate to severe, contingent on the mutation's nature and position. This research illuminates the influence of specific mutations on POR stability, underlining the necessity of understanding mutation-driven effects on enzyme stability to devise personalized therapeutic approaches for PORD patients. Future studies will involve the functional characterization of these mutant enzymes to further understand their impact on the POR enzyme's activity and stability.